Ecotoxicity of Tartrazine Yellow Dye in Danio rerio Embryos and Larvae After Multigenerational Exposure - da Silva, Janete [UNESP]; Fracácio-Francisco, Renata [UNESP] (Springer Nature, 2023)
The toxicological aspects of tartrazine yellow dye for human health are relatively well studied, but for aquatic environments, little is known. In order to understand whether the minimum and maximum safe concentrations for human ingestion (Codex Committee on Food Additives – CCFA) are also safe for aquatic biota, tests were carried out with Danio rerio, exposed to tartrazine yellow analytical standard 100% (AS) (50 mg. L−1 and 500 mg. L−1) and commercial standard 86% (CS) (50 mg. L−1) in multigenerational assays. Adults of D. rerio (F0 generation) were exposed (21 days) to the above concentrations, followed by mating and evaluation of the number of viable eggs laid (F1 generation). The remaining animals were exposed for 11 months. In both F1 and F2 generations, there was a surplus of eggs laid in the treatments in relation to the controls. However, embryos malformations and larval mortality rates were higher across the treatments. The multigenerational effect of the tartrazine yellow dye on D. rerio was confirmed by the pairwise ANCOVAS that always showed much smaller numbers of embryos at 96 hpf for the F2 generation. The results showed that concentrations considered safe for human ingestion represent risks to the aquatic biota.
Keywords: Azo Dye; Eggs; Embryos; Fish; Larval Development; Reproduction